Research Progress on Corrosion Behavior of Lightweight Automobile Self - Piercing Riveting Joint - WANG Fu-cai, LU Wei-zhong, YANG Hai (Cailiao Baohu)
Due to rapid developing of automobile lightweight, self-piercing riveting as a lightweight material joining technology is widely used. However, corrosion is an important issue which affects automobile safety and custom’s satisfaction, and corrosion of self-piercing riveting joint for car becomes research hotspot for self-piercing riveting technology in recent years. In this paper, equipment and preparation process of self-piercing riveting was briefly introduced, the research progress on corrosion behavior of joints such as aluminum alloy self-piercing riveted joints, steel aluminum dissimilar materials self-piercing riveted joints, carbon fiber / aluminum alloy were overviewed, corrosion problems of self-piercing riveting to be solved were pointed out. Besides, from the perspective of practical application and process conditions, the future research direction of self-piercing riveting joint corrosion was pointed out for improving the corrosion evaluation system and guiding the design life of self-piercing riveting joint.